RESISTENSI KULTURAL PEREMPUAN DALAM NOVEL HIKAYAT PUTI LIMAU MANIH: SINGA BETINA RIMBO HULU (Women Cultural Resistance In The Novel Hikayat Puti Limau Manih: Singa Betina Rimbo Hulu) - Syahril, Muhamad; Rahayu, Mundi (Kantor Bahasa Provinsi Sulawesi Tenggara, 2024)
Women resistance has become an important issue because the oppressive and hierarchical patriarchal culture has harmed women’s rights. This study aims to discuss women's cultural resistance represented in a literary work. This study uses a literary criticism approach to reach the goal by applying Naomi Wolf's feminist theory and James C. Scott's resistance theory. The data source for this research is a novel written by a female writer, Aprilia Wahyuni, entitled